The Determinants of COVID-19 Vaccine Acceptance in Sumatra - Sidarta, Cindy; Kurniawan, Andree; Lugito, Nata P H; Siregar, Jeremia Imanuel; Sungono, Veli; Heriyanto, Rivaldo Steven; Sieto, Novia Lauren; Halim, Devina Adella; Jodhinata, Claudia; Rizki, Saraswati Anindita; Sinaga, Terry Devita; Marcella, Chintya; Wijovi, Felix; Susanto, Billy; Marcella, Elizabeth; Wibowo, Johan; Anurantha, Jonathan Juniard; Imanuelly, Michelle; Indrawan, Michele; Heryadi, Nadia Khoirunnisa (Kesmas, 2022)
In light of the current coronavirus disease 2019 (COVID-19) vaccination programs being implemented worldwide, this study aimed to evaluate the COVID-19 vaccine acceptance survey in Indonesia conducted by the World Health Organization (WHO), the Ministry of Health of the Republic of Indonesia, the National Immunization Technical Advisory Group (NITAG), and the United Nations Children's Fund (UNICEF), published in November 2020. It was found that Sumatra Island having lower COVID-19 vaccine acceptance rates, with Aceh Province displaying the lowest level of vaccine acceptance. Thus, a cross-sectional study was conducted, and a logistic regression analysis was used to identify the factors affecting COVID-19 vaccine acceptance. Out of 368 respondents who participated in the survey, 143 (38.9%) accepted the vaccine, and 225 (61.1%) refused it. Vaccine safety concerns constituted the most reported reason for refusal (43.6%). This study also found that province of residence and basic immunization status were determinants of COVID-19 vaccine acceptance in Sumatra. Concerns regarding vaccine safety might be the reason for the low level of vaccination in Sumatra. Increased education and encouragement from healthcare professionals and regional authority figures can alleviate public concerns and improve vaccine acceptance.